August Wilhelm Ambros Musikaufsätze und -rezensionen 1872-1876, Bd. 2: 1874-1876 Historisch Kritische Ausgabe - Štědronská, Markéta (Hollitzer, 2019)
The present edition of musical essays and reviews by August Wilhelm Ambros (1816-1876) covers the years 1872-1876-a time that Ambros spent as a music reviewer for the Wiener Zeitung in Vienna. The second volume contains, in total, 126 essays from the years 1874-1876. It documents not only Ambros' position within Viennese music criticism of the 1870s, but also an important chapter in European musical history.